If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17f + 6 + -7f = 2 Reorder the terms: 6 + 17f + -7f = 2 Combine like terms: 17f + -7f = 10f 6 + 10f = 2 Solving 6 + 10f = 2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 10f = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 10f = 2 + -6 10f = 2 + -6 Combine like terms: 2 + -6 = -4 10f = -4 Divide each side by '10'. f = -0.4 Simplifying f = -0.4
| 0=3x^2-6x-297 | | (z^(5/2)*x^(-4))^(1/3) | | 9t^3-144t=0 | | (9a^3+a-3)-(6-3a^3-8a^2)= | | 8y^9-8y^8-96y^7=0 | | (z^(5/2)*x^-4)^(1/3) | | -(8y+2)-(-7y-3)=-6 | | x-y/4 | | x^2=3(2x-3) | | 3x^2-2y-8=0 | | -x-5y=15 | | 6(4x-3)=2(12x+9) | | 6+4t-2=7t+12-2t | | x^2/70 | | 3/2ln(16x^2)-2/5ln(2y^25) | | 9x+3=5-(5x-5) | | (x^2+x-5)= | | 6x-y=-32 | | 5h=t-5u | | -x^4-4x^2-16=0 | | t-5u=5h | | 9y+7y=96 | | -x^4+4x^2+16=0 | | (-9x+1)= | | (-9x+1)+(x^2+x-5)= | | 3-7(8-5x)=0 | | 4-6(7x+2)=9 | | (8/17)/(3/5) | | (5/8)*16 | | 8+6m-3=9m+9-2m | | (7/9)-(1/6) | | 5v^2+5=-26v |